A CURIOUS CONCESSION? AUSTRALIA’S WITHHOLDING TAX EXEMPTION FOR FRANKED DIVIDENDS - McMillan, Jim (2024)
This article considers the tax treatment of dividends paid by Australian companies to non resident shareholders, which benefit from a withholding tax exemption to the extent that the dividend is “franked” under Australia’s imputation system. The article considers the appropriateness of maintaining the withholding tax exemption now that more than 35 years have passed since the imputation system was introduced in Australia in 1987. It examines the original rationale for introducing the exemption and questions whether that rationale remains valid in 2023, given changes to corporate and individual tax rates in the intervening periods. The article also notes that to a potentially significant extent, the ongoing availability of this concession benefits foreign revenue authorities where non-resident shareholders live in countries which maintain a “classical” approach to taxation of dividends and allow credits for foreign withholding tax to be offset against tax liabilities in the country of residence. The article concludes that a comprehensive policy-based review of the concession is long overdue, that removal or modification of the exemption should be considered, and that the potential additional Australian tax revenue resulting from changes to the concession could be significant.